A mixed methods study to explore the association between psychosocial factors with mental well-being amongst IIUM dental students - Lim, Shea Lee (Kulliyyah of Nursing, International Islamic University Malaysia, 2022)
Background: Dentistry is considered to be a very stressful profession and this stress is said to begin during the dental students' undergraduate days. Chronic stress has been found to negatively impact one's overall well-being. High prevalence of common mental disorders including depression, stress and anxiety were common amongst dental students worldwide. Dental students are at risk of poor mental health which puts them at risk of poor mental well-being. Therefore, it is important that students who are at risk but clinically 'well' be identified so mental well-being promotion and early intervention can be introduced to prevent these students from falling through the gaps. This study aimed to explore the association between psychosocial factors and mental well-being amongst dental students and identify steps that can better support the students' mental well-being. Method: This study employed the mixed methods which consisted of a quantitative study and a qualitative study. The quantitative study provided information on the prevalence of depression, anxiety, stress and mental well-being and factors that are correlated with mental well-being. The qualitative study employed individual interviews to provide a deeper insight into the dental students' mental health experiences. Results: This study found that the over half the students had anxiety although the prevalence of stress and depression were low. Overall, the mental well-being level of the students are average. Gender, phase of study, history of psychiatric treatment, personality traits and mental health were correlated with their mental well-being. The interviews revealed the dental students' s individual struggles, how they coped, and suggestions on how they could be better supported. Conclusion: Findings from this study reveal opportunities to identify students who are at risk of developing poor mental well-being. The findings also help with better understanding of the dynamics of the students' mental well-being. Thus, the findings can be used for planning of mental well-being promotion programs.